Peanut mechanized digging regarding to plant population and soil water level - Zerbato, Cristiano [UNESP]; Silva, Vicente F. A. [UNESP]; Torres, Luma S. [UNESP]; Silva, Rouverson P. Da [UNESP]; Furlani, Carlos E. A. [UNESP] (Departamento de Engenharia Agrícola - UFCG, 2014)
The largest losses in mechanical harvesting of peanuts occur during the stage of digging, and its assessment is still incipient in Brazil. Therefore, the aim of this study was to evaluate the quantitative losses and the performance of the tractor-digger-inverter, according to soil water content and plant populations. The experiment was conducted in a completely randomized block design with a factorial scheme 2 x 3, in which the treatments consisted of two soil, water content (19.3 and 24.8%) and three populations of plants (86,111, 127,603 and 141,144 plants ha-1), with four replications. The quantitative digging losses and the set mechanized performance were evaluated. The largest amount of visible and total losses was found in the population of 141.144 plants ha-1 for the 19.3% soil water content. The harvested material flow and the tractor-digger-inverter performance were not influenced by soil water content and plant population. The water content in the pods was higher in 24.8% soil water content only for the population of 86,111 plants ha-1; the yield was higher in the populations of 141.144 and 127.603 plants ha-1, in the 19.3 e 24.8% soil water content, respectively.

As maiores perdas na colheita mecanizada ocorrem na operação do arranquio sendo que sua avaliação ainda é incipiente no Brasil. Objetivou-se, portanto, neste trabalho, avaliar as perdas quantitativas e o desempenho do conjunto trator-arrancador-invertedor em função de teores de água do solo e populações de plantas. O experimento foi conduzido em delineamento experimental em blocos casualizados com esquema fatorial 2 x 3 em que os tratamentos foram constituídos de dois teores de água no solo (19,3 e 24,8%) e três populações de plantas (86.111, 127.603 e 141.144 plantas ha-1), com quatro repetições. Avaliaram-se as perdas quantitativas no arranquio e o desempenho do conjunto mecanizado. A maior quantidade de perdas visíveis e totais foi encontrada na população de 141.144 plantas ha-1 para o teor de água do solo de 19,3%. O fluxo de material colhido e o desempenho do conjunto trator-arrancador-invertedor não foram influenciados pelos teores de água do solo e populações de plantas. O teor de água das vagens foi maior no teor de água do solo de 24,8% somente para a população de 86.111 plantas ha-1; a produtividade foi maior nas populações de 141.144 e 127.603, nos teores de água de 19,3 e 24,8%, respectivamente.
Arranquio mecanizado de amendoim associado à população de planta e ao teor de água do solo
Keywords: Arachis hypogaea L; crop losses; digger-inverter; operating performance; Arachis hypogaea L.; Arrancador-invertedor; Desempenho operacional; Perdas na colheita